Newspaper Coverage of Rabies in Malaysia: Persuasive Appeals and Health Belief Constructs - Su Hie, Ting; Nur Izzati, Md Jaafar (Springer Nature, 2025)
Rabies presents biosecurity concerns in Malaysia that was rabies-free for 20 years prior to 2017. This study examines how Malaysian newspapers framed rabies outbreaks in 2017 and 2022, focussing on rhetorical appeals and content in The Star (national) and Borneo Post (regional). A total of 89 articles were identified using ‘‘rabies’’, ‘‘dog’’ and ‘‘canine’’ as search terms. A time-series comparison revealed that media attention was driven more by news value than by disease severity. When rabies re-emerged after two decades, emotional appeals and severity was emphasised in the 63 news articles on rabies (20 BP, 43 TS). By 2022, only 26 news articles (13 BP, 13 TS) on rabies were identified despite more cases and deaths, and there was a shift towards logical appeals and the content was mostly control measures. The cross-newspaper comparison further showed that The Star emphasised susceptibility, warning readers of personal risk, while Borneo Post stressed severity but both newspapers emphasised protective actions. The findings suggest that disease framing of rabies in newspapers should sustain use of human stories to motivate preventive action after the initial shock of an infectious disease outbreak has passed.